2006
DOI: 10.1152/jn.00842.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Neural Function of Repleting Vitamin E–Deficient Rats With α-Tocopherol

Abstract: Effects on neural function of repleting vitamin E-deficient rats with ␣-tocopherol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…2, 86). Interestingly, a previous study showed a similar, age‐related effect on body weights of rats fed an αT‐depleted diet 38. Autopsy of the old αTTP‐KO mice was remarkable for decreased amount of abdominal white adipose tissue.…”
Section: Future Directionsmentioning
confidence: 65%
See 1 more Smart Citation
“…2, 86). Interestingly, a previous study showed a similar, age‐related effect on body weights of rats fed an αT‐depleted diet 38. Autopsy of the old αTTP‐KO mice was remarkable for decreased amount of abdominal white adipose tissue.…”
Section: Future Directionsmentioning
confidence: 65%
“…Equally noteworthy is that 1 mg of αT/Kg of diet is sufficient to prevent the deficiency symptoms. It seems that larger amounts of dietary αT supplements, 36 mg/Kg diet, are necessary to reverse the symptoms caused by dietary αT deficiency 38. The effects of the differences in micronutrient composition on “stability” of other labile dietary constituents, such as vitamin A, essential aminoacids and unsaturated fatty acids, remain uncharacterized.…”
Section: Nutritional Myopathy and Ataxia In Animal Models Of Dietarmentioning
confidence: 99%
“…A hierarchical cluster analysis further suggested that α-TTP might be required for normal functioning of glial cells and oligodendrocytes (Gohil et al 2004). A more detailed investigation of α-tocopherol-regulated genes in the brain will finally provide a molecular basis for neurological disorders that develop in vitamin E deficiency (Hayton et al 2006).…”
Section: Functions Of Vitamin Ementioning
confidence: 99%
“…Previous studies in rodents [49] and humans [50] have suggested that chronic AT-deficiency results in initial loss of neural functions. Hence, the transcriptomic responses of skeletal muscles of ATTP-KO mice described here may be in addition to neural deficits.…”
Section: Discussionmentioning
confidence: 99%